Fatty Acids, Lipid Mediators, and T-Cell Function - de Jong, Anja J.; Kloppenburg, Margreet; Toes, René E. M.; Ioan-Facsinay, Andreea (Frontiers in Immunology, 2014)
Research toward the mechanisms underlying obesity-linked complications has intensified during the last years. As a consequence, it has become clear that metabolism and immunity are intimately linked. Free fatty acids and other lipids acquired in excess by current feeding patterns have been proposed to mediate this link due to their immune modulatory capacity. The functional differences between saturated and unsaturated fatty acids, in combination with their dietary intake are believed to modulate the outcome of immune responses. Moreover, unsaturated fatty acids can be oxidized in a tightly regulated and specific manner to generate either potent pro-inflammatory or pro-resolving lipid mediators. These oxidative derivatives of fatty acids have received detailed attention during the last years, as they have proven to have strong immune modulatory capacity, even in pM ranges. Both fatty acids and oxidized fatty acids have been studied especially in relation to macrophage and T-cells functions. In this review, we propose to focus on the effect of fatty acids and their oxidative derivatives on T-cells, as it is an active area of research during the past 5 years. The effect of fatty acids and their derivatives on activation and proliferation of T-cells, as well as the delicate balance between stimulation and lipotoxicity will be discussed. Moreover, the receptors involved in the interaction between free fatty acids and their derivatives with T-cells will be summarized. Finally, the mechanisms involved in modulation of T-cells by fatty acids will be addressed, including cellular signaling and metabolism of T-cells. The in vitro results will be placed in context of in vivo studies both in humans and mice. In this review, we summarize the latest findings on the immune modulatory function of lipids on T-cells and will point out novel directions for future research.